Effects of myrrh on intra-oral mucosal wounds compared with tetracycline- and chlorhexidine-based mouthwashes - Al-Mobeeriek A (Dove Medical Press, 2011)
Azizah Al-MobeeriekDepartment of Oral Medicine and Diagnostic Sciences, College of Dentistry, King Saud University, Riyadh, Saudi ArabiaAim: To evaluate the effect of myrrh compared with chlorhexidine gluconate- and tetracycline-containing mouthwashes on wound healing over time in an animal model.Methods: A unilateral incision on the right buccal mucosa was made, and the wound was irrigated with myrrh-, chlorhexidine gluconate-, or tetracycline-based mouthwashes at various time intervals. Clinical and histological examination was performed for all the groups.Results: It was found that the myrrh suspension promotes healing and repair of damaged tissue when used over a short period of time (less than 2 weeks) and in a low-concentration suspension; however, it can have harmful effects if used in excess or over a long period of time.Conclusion: Further studies will also be required to study these effects and their mechanism of action in detail.Keywords: myrrh, chlorhexidine gluconate, tetracycline, mouthwash, wound healing